2015
DOI: 10.1111/gcb.13097
|View full text |Cite
|
Sign up to set email alerts
|

Continent‐scale global change attribution in European birds ‐ combining annual and decadal time scales

Abstract: Species attributes are commonly used to infer impacts of environmental change on multiyear species trends, e.g. decadal changes in population size. However, by themselves attributes are of limited value in global change attribution since they do not measure the changing environment. A broader foundation for attributing species responses to global change may be achieved by complementing an attributes-based approach by one estimating the relationship between repeated measures of organismal and environmental chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 67 publications
0
56
0
Order By: Relevance
“…Thus, in general mountain birds are doing less bad than farmland birds, but clearly worse than forest birds in Europe. The severe declines of farmland birds are mainly driven by intensification of agriculture rather than climate change (Butler, Boccacio, Gregory, Voříšek, & Norris, ; Eglington & Pearce‐Higgins, ; Jørgensen et al, ). However, in case of mountain birds, climate change can have a larger impact as the climatic niche of especially mountain specialists is shrinking, highlighted by the relatively fast declines of mountain species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in general mountain birds are doing less bad than farmland birds, but clearly worse than forest birds in Europe. The severe declines of farmland birds are mainly driven by intensification of agriculture rather than climate change (Butler, Boccacio, Gregory, Voříšek, & Norris, ; Eglington & Pearce‐Higgins, ; Jørgensen et al, ). However, in case of mountain birds, climate change can have a larger impact as the climatic niche of especially mountain specialists is shrinking, highlighted by the relatively fast declines of mountain species.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in land cover (Mayfield et al, 2010;Jørgensen et al, 2016), introduction of exotic species (Sax & Gaines, 2003, anthropogenic climate change (Men endez et al, 2006;La Sorte & Jetz, 2010a;Jørgensen et al, 2016), and targeted conservation actions and federal efforts to restore critical habitats (King et al, 2006) might all have contributed to the observed increases in avian diversity. Similar increases were recently reported by Schipper et al (2016) for a slightly shorter version of the BBS dataset; that study, however, did not detect declines in biodiversity over the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…We weighted the model by the inverse of the average standard error of the two population indices used to calculate growth rates to correct for the degree of uncertainty in the response variable (Jørgensen et al . ). The results of the model with the weights were qualitatively the same as of the same model without weighting, and here only the results of the weighted model are shown.…”
Section: Methodsmentioning
confidence: 97%